The Journal of Antibiotics Official journal of Japan Antibiotics Research Association (JARA), affiliated by the Society for Actinomycetes Japan - Tatsuta, Kuniaki; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Springer Nature.)
The Journal of Antibiotics seeks to promote research on antibiotics and related types of biologically active substances and publishes Articles, Review Articles, Brief Communication, Correspondence and other specially commissioned reports. The Journal of Antibiotics accepts papers on biochemical, chemical, microbiological and pharmacological studies. However, studies regarding human therapy do not fall under the journal$1 (Bs scope. Contributions regarding recently discovered antibiotics and biologically active microbial products are particularly encouraged. Topics of particular interest within the journal's scope include, but are not limited to, those listed below: - Discovery of new antibiotics and related types of biologically active substances - Production, isolation, characterization, structural elucidation, chemical synthesis and derivatization, biological activities, mechanisms of action, and structure-activity relationships of antibiotics and related types of biologically active substances - Biosynthesis, bioconversion, taxonomy and genetic studies on producing microorganisms, as well as improvement of production of antibiotics and related types of biologically active substances - Novel physical, chemical, biochemical, microbiological or pharmacological methods for detection, assay, determination, structural elucidation and evaluation of antibiotics and related types of biologically active substances - Newly found properties, mechanisms of action and resistance-development of antibiotics and related types of biologically active substances.s
Keywords: Organic chemistry; Bioorganic chemistry; Medicinal chemistry; Life sciences; Microbiology; Bacteriology; Life Sciences, general; Microbiology; Medicinal Chemistry; Organic Chemistry; Bacteriology; Bioorganic Chemistry